Genome-Wide Identification and Characterization of the GRAS Gene Family in Lettuce Revealed That Silencing LsGRAS13 Delayed Bolting - Li Chen; Yong Qin; Shuangxi Fan (Plants, 2024)
Lettuce is susceptible to high-temperature stress during cultivation, leading to bolting and affecting yield. Plant-specific transcription factors, known as GRAS proteins, play a crucial role in regulating plant growth, development, and abiotic stress responses. In this study, the entire lettuce LsGRAS gene family was identified. The results show that 59 LsGRAS genes are unevenly distributed across the nine chromosomes. Additionally, all LsGRAS proteins showed 100% nuclear localization based on the predicted subcellular localization and were phylogenetically classified into nine conserved subfamilies. To investigate the expression profiles of these genes in lettuce, we analyzed the transcription levels of all 59 LsGRAS genes in the publicly available RNA-seq data under the high-temperature treatment conducted in the presence of exogenous melatonin. The findings indicate that the transcript levels of the LsGRAS13 gene were higher on days 6, 9, 15, 18, and 27 under the high-temperature (35/30 °C) treatment with melatonin than on the same treatment days without melatonin. The functional studies demonstrate that silencing LsGRAS13 accelerated bolting in lettuce. Furthermore, the paraffin sectioning results showed that flower bud differentiation in LsGRAS13-silenced plants occurred significantly faster than in control plants. In this study, the LsGRAS genes were annotated and analyzed, and the expression pattern of the LsGRAS gene following melatonin treatment under high-temperature conditions was explored. This exploration provides valuable information and identifies candidate genes associated with the response mechanism of lettuce plants high-temperature stress.